(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article discusses the concept of the crime of intrusion, the reforms carried out in our country to combat crime, indicators of crime, aspects that need to be studied about the victims of the crime, the reasons for the commission of the crime of intrusion and the conditions that allowed them to be committed, with the features of the operational staff’s contact unit with the victims of the violent crimes , psychological characteristics of the persons who committed the crime of aggression are noted.